A cultura como matriz pedagógica na proposta curricular das escolas localizadas no campo - Machado, Rita das Dores (2016)
This work presents the concepts of culture that guide the process of drafting the proposed curriculum of schools located in the countryside, in the municipality of Tijucas do Sul. It identifies existing challenges and perspectives that can be built in order to produce a compromised proposal to the critical training and development of the cultural identity of the subjects of the field, as well as the production of scientific knowledge drivers of development and permanence of man in the field. The objective of this research is to analyze aspects of the local culture are present in the curriculum proposals of the schools located in the countryside in Tijucas do Sul and what their influence in this context. How the specific objectives if we list-following: 1- identify the PPC's (Proposals Pedagogical Curriculum) schools located in the countryside in the municipality of Tijucas do Sul aspects referred to the local culture. 2 analyze the influence of aspects of local culture in schools located in the field. The participatory research was being developed through interviews, document analysis and focus groups with teachers of municipal Tijucas do Sul. The theoretical references used in the studies are based on the writings of Arroyo (2011) that address Pedagogic Matrices and concepts labor, Land, Culture, Experience, Oppression and Social Movements. In addition to this author, are for reference Souza (2010) and Caldart (2007), reflecting on the characteristics and historical construction of identities of Rural Education and Rural Education, and authors such as Williams (2011), Gramsci (1991) and Cuche ( 1999), conceptualizing and reflecting on the term culture and dichotomies. The research revealed the importance of realizing the field of education as a means of training committed to recognize the subjects, their culture and identity, and so create alternatives for another pedagogical practice is possible, and that has as objective to their emancipation.